Highly sensitive visual detection of mutant DNA based on polymeric nanoparticles-participating amplification. Issue 116 (15th December 2016) - Cui, Yanjun; Zhuang, Dequan; Tan, Tianwei; Yang, Jing
Abstract : Taking advantage of the nanoparticles' large surface area and structural repeating characteristics, polymeric nanoparticles-participating polymerization-based amplification system was designed to enhance the sensitivity of detection. Abstract : Taking advantage of the large surface area of nanoparticles and the structural repeating characteristics of the polymer, one type of polymeric nanoparticles-participating polymerization-based amplification system was created to enhance the sensitivity of detection. The polymeric nanoparticles with reducing poly(ascorbyl acrylate) as a hydrophilic shell could react with H2 O2 to rapidly initiate redox polymerization of the monomer hydroxyl ethylacrylate. Such a redox polymerization system for molecular detection could render a visually discernible polymer film at the target DNA as low as 100 fM. Furthermore, a cascade of glucose oxidase (GOx) catalyzing the oxidation of glucose (consuming oxygen and generating H2 O2 in situ ) and the nanoparticles-participating redox polymerization was set up to enable this assay to be performed in open air conditions. This assay was used to detect a non-small cell lung cancer p53 sequence and displayed excellent differentiation ability for a single-base mismatch as well. It is anticipated that such a design will provide a useful platform for the user-friendly, ultrasensitive and visual detection of a broad range of biomolecules.